2019
DOI: 10.1183/13993003.01886-2019
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of active tuberculosis during pregnancy and postpartum: a register-based cohort study in Sweden

Abstract: RationaleStudies investigating the risk of active tuberculosis (TB) in association with pregnancy have not been conclusive. We aimed to investigate this risk in a large retrospective register-based cohort study in Sweden.MethodsData from women of 15–49 years of age who had given birth in Sweden between 2005 and 2013 were extracted from the national childbirth register and linked to the national TB register. Cohort time was divided into three exposure periods: during pregnancy, six months (180 days) postpartum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 18 publications
1
42
1
Order By: Relevance
“…those without this profile) at an increased risk of TB progression and would further support the idea of LTBI as a spectrum where subgroups of LTBI+ are protected from progression while others are not (9, 10). In addition, future studies would also need to determine whether this relationship of the systemic immune profile with TB progression is causal as it could partly explain the increased risk of Mtb progression during pregnancy and post-partum (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…those without this profile) at an increased risk of TB progression and would further support the idea of LTBI as a spectrum where subgroups of LTBI+ are protected from progression while others are not (9, 10). In addition, future studies would also need to determine whether this relationship of the systemic immune profile with TB progression is causal as it could partly explain the increased risk of Mtb progression during pregnancy and post-partum (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…It is not currently known whether there is a difference in systemic inflammation between LTBI+ and LTBI− pregnant women, and how this might change by trimester of pregnancy. Furthermore, LTBI+ women have a higher risk of Mtb progression during pregnancy and post-partum, but the reasons are not clear (15)(16)(17). The immune profile during pregnancy, including the systemic inflammatory milieu, may inform on potential changes to immunity that increase susceptibility to TB disease during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…According to recent WHO reports, about one-quarter of the world's population is estimated to have LTBI and only 5-10% of these individuals eventually develop active TB (World Health Organization, 2019). However, the risk of developing active TB as a result of reactivation of the LTBI could substantially increase in the presence of several predisposing factors such as Human immunodeficiency virus (HIV) infection and pregnancy (World Health Organization, 2019;Jonsson et al, 2020). HIV infection diminishes the Th1 cell-mediated immune response Abbreviations: TB, tuberculosis; LTBI, latent tuberculosis infection; HIV, Human immunodeficiency virus; M. tuberculosis, Mycobacterium tuberculosis; CD, cluster of differentiation; IFN, interferon; BCG, Bacille Calmette-Guérin; TST, tuberculin skin test; ELISA, enzyme-linked immunosorbent assay; QFTGIT, QuantiFERON-TB Gold In-Tube; PPD, purified protein derivative; ESAT-6, Early secreted antigen target-6; CFP-10, Culture filtrate protein-10; IQR, interquartile range; CDC, Center for Disease Control and Prevention; WHO, World Health Organization. to M. tuberculosis, while pregnancy deepens this suppression of anti-mycobacterial responses in HIV-positive individuals (Birku et al, 2020;Amelio et al, 2019;Mofenson and Laughon, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated this increased risk of TB in PWWH, particularly postpartum [ 26 , 27 ]. Women without HIV also have an increased TB risk during pregnancy, and an even greater risk postpartum [ 28 , 29 ]. How pregnancy- and postpartum-induced biomarker changes affect immune activation pathways known to predict morbidity and mortality in HIV remains incompletely understood [ 30 ].…”
mentioning
confidence: 99%